2000
DOI: 10.1046/j.1525-139x.2000.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Effects of a High Peritoneal Transport Rate

Abstract: Recent studies have shown that patients with high peritoneal transport characteristics have substantially increased morbidity and mortality. This finding is counter-intuitive, since HTs will a priori achieve higher clearances. There are many possible causes: increased protein losses with consequent hypoalbuminemia; poor ultrafiltration capacity causing fluid retention, ventricular hypertrophy and hypertension; increased glucose absorption leading to anorexia, hyperinsulinism, and local AGE formation; and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
1
14
1
Order By: Relevance
“…19 Therefore, the concept of chronic inflammation in influencing peritoneal transport rate had been proposed. 7 Previous study had demonstrated that the higher peritoneal transport rate status, regardless of before dialysis or with time after starting PD, was positively correlated with serum CRP level but had a reciprocal relationship with serum albumin levels, which both were as surrogate markers of inflammation. 20,21 Furthermore, Pecoits-Filho et al reported the plasma and dialysate IL-6 levels were significantly higher in patients with increasing peritoneal transport rate.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…19 Therefore, the concept of chronic inflammation in influencing peritoneal transport rate had been proposed. 7 Previous study had demonstrated that the higher peritoneal transport rate status, regardless of before dialysis or with time after starting PD, was positively correlated with serum CRP level but had a reciprocal relationship with serum albumin levels, which both were as surrogate markers of inflammation. 20,21 Furthermore, Pecoits-Filho et al reported the plasma and dialysate IL-6 levels were significantly higher in patients with increasing peritoneal transport rate.…”
Section: Discussionmentioning
confidence: 96%
“…Despite pathogenic effects of high peritoneal transport status being documented, 7 the determinants on the peritoneal transport characteristics have not been well clarified. The clinical factors (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who have a greater rate of membrane solute transport are classified as high (or fast) transporters, and will tend to have enhanced clearance of small solutes, such as urea and creatinine, early in short dwells. However, these patients will have larger peritoneal loss of protein, will be more likely to fluid overload as a result of rapid reabsorption of glucose from the dialysate and subsequent ultrafiltration dysfunction, and will have greater systemic exposure to glucose (15-19). In addition, high transporters have been associated with poor nutritional status, more prevalent comorbid diseases, and chronic inflammation (3, 9-13).…”
Section: Discussionmentioning
confidence: 99%
“…The most common functional alteration during long-term PD is increased peritoneal small-solute transport rate measured by dialysate-to-plasma (D/P) ratios or mass transfer area coefficients (MTAC) [ 3 , 4 ], which is the major contributor to impaired ultrafiltration and ultimately discontinuation of treatment [ 5 ]. It has been well appreciated that high D/Pcr represented an independent risk factor for mortality and technique failure in PD patients [ 6 8 ] as a consequence of increased glucose absorption from peritoneal cavity and inadequate dialysis, leading to suboptimal ultrafiltration capacities, fluid overload and malnutrition [ 9 ]. On the other hand, patients may lose approximately 5 g total protein or 4 g albumin daily from the peritoneal cavity during PD therapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%